Cloning, preparation and preliminary crystallographic studies of penicillin V acylase autoproteolytic processing mutants - Chandra, P. M.; Brannigan, James A.; Prabhune, Asmita; Pundle, A.; Turkenburg, J. P.; Dodson, Guy G.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2005)

Cloning, purification, crystallization and preliminary structural studies of penicillin V acylase from Bacillus subtilis - Rathinaswamy, P.; Pundle, A. V.; Prabhune, Asmita; SivaRaman, H.; Brannigan, James A.; Dodson, Guy G.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology Communications, 2005)
{Penicillin acylase proteins are amidohydrolase enzymes that cleave penicillins at the amide bond connecting the side chain to their beta-lactam nucleus. An unannotated protein from Bacillus subtilis has been expressed in Escherichia coli, purified and confirmed to possess penicillin V acylase activity. The protein was crystallized using the hanging-drop vapour-diffusion method from a solution containing 4 M sodium formate in 100 mM Tris-HCl buffer pH 8.2. Diffraction data were collected under cryogenic conditions to a spacing of 2.5 A. The crystals belonged to the orthorhombic space group C222(1), with unit-cell parameters a = 111.0

Cloning, overexpression, crystallization and preliminary X-ray crystallographic analysis of a slow-processing mutant of penicillin G acylase from Kluyvera citrophila - Varshney, Nishant Kumar; Ramasamy, Sureshkumar; Brannigan, James A.; Wilkinson, Anthony J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2013)
{Kluyvera citrophila penicillin G acylase (KcPGA) has recently attracted increased attention relative to the well studied and commonly used Escherichia coli PGA (EcPGA) because KcPGA is more resilient to harsh conditions and is easier to immobilize for the industrial hydrolysis of natural penicillins to generate the 6-aminopenicillin (6-APA) nucleus, which is the starting material for semi-synthetic antibiotic production. Like other penicillin acylases, KcPGA is synthesized as a single-chain inactive pro-PGA, which upon autocatalytic processing becomes an active heterodimer of alpha and beta chains. Here, the cloning of the pac gene encoding KcPGA and the preparation of a slow-processing mutant precursor are reported. The purification, crystallization and preliminary X-ray analysis of crystals of this precursor protein are described. The protein crystallized in two different space groups, P1, with unit-cell parameters a = 54.0